The incidence of childhood leukaemia around the La Hague nuclear waste reprocessing plant (France): a survey for the years 1978–1998. Issue 7 (1st July 2001) - Guizard, A-V; Boutou, O; Pottier, D; Troussard, X; Pheby, D; Launoy, G; Slama, R; Spira, A; ,
Abstract : BACKGROUND: A previous study has suggested an increased incidence rate of leukaemia from 1978 to 1992 in people aged 0 to 24 years and living in the vicinity of the La Hague nuclear waste reprocessing plant without considering age and cytological type. SETTING: The Nord Cotentin region (France) and the island of Alderney (United Kingdom). STUDY OBJECTIVE: To describe the occurrence of leukaemia for each age group and cytological type from 1978 to 1998 in the same area, using accurate reference incidence rates and adequate estimation of the at risk population. DESIGN: A geographical study of incidence using three zones defined according to their distance from the site (0 to 10 km: Beaumont-Hague electoral ward, 10 to 20 km and 20 to 35 km) has been conducted. The risk of leukaemia was estimated from the standardised incidence ratio (SIR) of the number of cases observed to the number expected. Exact 95% confidence intervals (CI) have been computed. PARTICIPANTS: All people under the age of 25 years living in the study region between 1978 and 1998. MAIN RESULTS: The observed number of cases of leukaemia in the study region as a whole was consistent with the expected value (SIR=1.03; 95%CI: 0.73, 1.41). No cases were observed on Alderney. The SIR in the Beaumont-Hague electoral ward was 2.17 (95%CI: 0.71, 5.07). The highest SIR was observed in the 5 to 9 years age group (SIR=6.38; 95%CI: 1.32, 18.65). This consists in acute lymphoblastic leukaemia cases. CONCLUSION: This study indicates an increased incidence of leukaemia in the area situated at less than 10 km from the plant. Monitoring and further investigations should be targeted at acute lymphoblastic leukaemia occurring during the childhood incidence peak (before 10 years) in children living near the La Hague site and may be other nuclear reprocessing plants.